Answer:
6
Explanation:
we would like to compute the following limit of a sequence below:
![\displaystyle\lim_(n \to \infty) (3)/(√(4n^2+2n)-2n)](https://img.qammunity.org/2022/formulas/mathematics/high-school/1zktbth9pp3l961u6ztwl0topz6glsk2q2.png)
before we do so,here some formulas below which is required:
![\displaystyle \lim _(x \to c) (f(x))/(g(x)) = ( \displaystyle \lim _(x \to c)f(x) )/(\displaystyle \lim _(x \to c)g(x) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/r49ot0dkn2lv7pcy5bj8azwyvxdq1mnf7n.png)
finding the limit:
utilize the first formula:
![( \displaystyle\lim_(n \to \infty)3)/( \displaystyle\lim_(n \to \infty)√(4n^2+2n)-2n)](https://img.qammunity.org/2022/formulas/mathematics/high-school/kabjja1xgc1r4teg79gbcaldktfi5topz1.png)
finding the limit of numerator:
Any limit of a constant is equal to the constant therefore the limit of the numerator is equal to 3
finding the limit of the denominator:
rationalize it:
![\displaystyle\lim_(n \to \infty) \left(√(4n^2+2n)-2n * \frac{ \sqrt{ {4n}^(2) + 2n } + 2n}{ \sqrt{{4n}^(2) + 2n } + 2n } \right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/7o9qs6l00tv1w49sl5v012nglb0qa9rrfk.png)
simplify multiplication:
![\displaystyle\lim_(n \to \infty) \left( \frac{ 2n}{ \sqrt{{4n}^(2) + 2n } +2n} \right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/o29tte5nxoxvwsxenfge88li1k5yj3ypfq.png)
remember that,for limits to infinity, terms less than the highest degree of the numerator or denominator can be disregarded thus we can drop 2n of the square root expression
![\rm\displaystyle\lim_(n \to \infty) \left( \frac{ 2n}{ \sqrt{{4n}^(2) + 2n } + 2n} \right) \implies \lim_(x\to \infty) (2n)/(2n+2n) \implies \lim_(x\to \infty)(2n)/(4n)\implies\boxed{(1)/(2)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/66vl7zbvy1xtli4qu1rqzk2hj7mzjy9m7o.png)
since we've figured out the limit of the both numerator and denominator therefore substitute:
![(3)/( (1)/(2) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/lseitfnijykdufrswpnwphy1r8wm8we4ux.png)
simplify complex fraction:
![6](https://img.qammunity.org/2022/formulas/mathematics/college/fmdysmn9ncwbp2rzfvvvxwe4637rny37vp.png)
hence,
![\displaystyle\lim_(n \to \infty) (3)/(√(4n^2+2n)-2n)=\boxed{6}](https://img.qammunity.org/2022/formulas/mathematics/high-school/754z73wwdjv390eqnz0cs37w5tab4hfeh5.png)